(untitled) (Journal of the College of Basic Education, 2022)
Research problem: The research problem is determined by asking the following question:What role does contemporary digital printing play as an advanced technology in terms of aesthetic impact on graphic design?Research importance: The importance of research is determined by the following:- Identifying the means of contemporary digital technology and what it represents of an urgent necessity in the development of contemporary printing technology and its effects in showing the aesthetic aspect of the printed matter.Research objective: The research aims to reveal the aesthetics of digital printing and its role in achieving the attractiveness and quality of contemporary print.